Financial modelling in project finance - Bulatović Jelena (Ekonomski Pogledi, 2014)
The introduction part gives a brief review and basic characteristics of Project Finance. The framework is consisted of the financial model, role of each party in its making and application. It shows how the financial model is being used by the investors in order to calculate their income, by creditors to calculate level of debt ratio and to create a basis for a sensitivity analysis. It provides an overview and the explanation of inputs (macro-economic presumptions, project expense and financing structure, operative income and expenses, withdrawal of a loan and debt servicing, accounting and taxes) and outputs of the financial model (balance sheets, income statements, cash flow statement, debt service ratios and investor's return of equity).